Challenges in Understanding Descriptive Texts Among Eighth-Grade Students at MTs Swasta Darul Akhiroh, Bonan Dolok - Pratiwi, Summi; Maharani; Meidipa, Lisa Fitri (Yayasan Kajian Riset dan Pengembangan RADISI, 2024)
This study investigates the challenges eighth-grade students face in comprehending descriptive English texts at MTs Swasta Darul Akhiroh, Bonan Dolok, during the first semester of the 2022-2023 academic year. The research specifically examines internal and external factors influencing reading comprehension skills among a sample of 30 students. Employing a qualitative research methodology with a descriptive approach, the study utilizes cluster sampling to select the entire class as the research sample. Data collection instruments include questionnaires to assess the classroom environment and students' attitudes towards reading English texts, alongside tests designed to evaluate students' proficiency in various aspects of reading comprehension such as identifying main ideas, supporting details, vocabulary context, and answering detailed questions. The findings reveal significant difficulties in reading comprehension among the students, attributed to a lack of vocabulary, the length of texts, and a general disinterest in engaging with the reading material actively. Test results indicate particular weaknesses in answering detailed questions, with only 27.7% of students performing satisfactorily in this area. This highlights a critical area for intervention, suggesting a need for targeted strategies to enhance students' reading skills and overall engagement with English texts.